Research of historical landscape by using old maps with focus to its positional accuracy - Frajer, Jindřich (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2011)
Old maps are an important historical source for exploring historical landscapes. They are often used as cartographic bases for studying structural changes and reconstruction of land use. This study is concerned with comparison of positional accuracy of a set of Žold maps' as compared to present-day maps. Determination of positional deviations defines the degree of precision of the old map and its potential for its use in GIS applications. The total of ten unique historical maps in different scales from the Čáslav region of Central Bohemia were examined regarding its positional accuracy.
Keywords: cartography; Czech Republic; Češka; history; kartografija; landscape; pokrajina; raba tal; regional geography; regionalna geografija; spremembe; Subdivisions of the Kingdom of Yugoslavia; zgodovina